Improving the Direct Electron Transfer in Monolithic Bioelectrodes Prepared by Immobilization of FDH Enzyme on Carbon-Coated Anodic Aluminum Oxide Films - Castro-Muñiz, Alberto; Hoshikawa, Yasuto; Komiyama, Hiroshi; Nakayama, Wataru; Itoh, Tetsuji; Kyotani, Takashi (Frontiers in Materials, 2016)
The present work reports the preparation of binderless carbon-coated porous films and the study of their performance as monolithic bioanodes. The films were prepared by coating anodic aluminum oxide (AAO) films with a thin layer of nitrogen-doped carbon by chemical vapor deposition. The films have cylindrical straight pores with controllable diameter and length. These monolithic films were used directly as bioelectrodes by loading the films with D-fructose dehydrogenase (FDH), an oxidoreductase enzyme that catalyzes the oxidation of D-fructose to 5-keto-D-fructose. The immobilization of the enzymes was carried out by physical adsorption in liquid phase and with an electrostatic attraction method. The latter method takes advantage of the fact that FDH is negatively charged during the catalytic oxidation of fructose. Thus the immobilization was performed under the application of a positive voltage to the CAAO film in a FDH-fructose solution in McIlvaine buffer (pH 5) at 25 ºC. As a result, the FDH modified electrodes with the latter method show much better electrochemical response than that with the conventional physical adsorption method. Due to the singular porous structure of the monolithic films, which consists of an array of straight and parallel nanochannels, it is possible to rule out the effect of the diffusion of the D-fructose into the pores. Thus the improvement in the performance upon using the electrostatic attraction method can be ascribed not only to a higher uptake, but also to a more appropriate molecule orientation of the enzyme units on the surface of the electrodes.